Towards a Renewed View of Marshall McLuhan’s Work and Thought in Latin America - Islas, Octavio (2021)
The central theme of our text is the presence of a shadow in the communication academy in Latin America: the shadow of Marshall McLuhan. In the first section, we refer to some anecdotes about McLuhan’s participation in the First World Congress on Communication, held in 1974, in Mexico. This allows us to narrate how the first degree in communication sciences was conceived. In the second section, we identify some events that we consider particularly significant in the recovery of McLuhan’s work and thought in Latin America. In Latin America we must recover the questions that this wonderful visionary and philosopher of communication formulated. This will allow us to recover a large part of the time we have lost.